Online sexual grooming : a cross-cultural perspective on online child grooming victimization - Ferreira, Fátima Abreu (2011)
New technologies, particularly the Internet, are valuable educational, entertaining and connection resources but they also create a new and mostly unregulated environment that exposes children to a multiplicity of risks: violence, bullying, misinformation and sexual predators, amongst others. In fact, the unmonitored interface between children and adults has led to a growing concern about the Internet´s role as a tool for adults wishing to sexual exploit and abuse young people. This research intends to examine the national prevalence and scale of online child sexual grooming, how it takes place and the core characteristics (behaviors, frequency, and duration) of the online grooming victimization. In order to accomplish a wider and more comprehensive view of this phenomenon, we have made a cross cultural comparison between Portugal, Spain and the United Kingdom that are classified at a medium-high level of access to new technologies and exposure to online risks. To achieve our goals, we have developed a questionnaire (Online Victimization Assessment) that we have applied to a representative sample of youngsters from ten to eighteen years old, from Portugal, Spain and the United Kingdom. Unfortunately, considering that we are still applying the mentioned questionnaire, we can´t present its results at the moment of the abstract submission but will be able to do it in the event.